Present status, production constraints and future research strategies in oilseed brassica: Present status, production constraints and future research strategies in oilseed brassica - MAHAK SINGH; AMIT TOMAR; SANJAY KUMAR (Journal of Oilseeds Research, 2023)
The oleiferous Brassica species, commonly known as rapeseed-mustard, are one of the economically important agricultural commodities. Rapeseed-mustard comprising eight different species viz., Indian mustard, toria, yellow sarson, brown sarson, gobhi sarson, karan rai, black mustard and taramira, are being cultivated in 53 countries spreading all over the globe. The oil and protein content varies from 37 to 49% and 22-28%, respectively. The seed and oil are used as condiment in the preparation of pickles and for flavouring curries and vegetables. The oil is utilized for human consumption throughout the northern India in cooking and frying purposes. It is also used in the preparation of hair oils and medicines. It is used in soap making, in mixtures with mineral oils for lubrication. Rapeseed oil is used in the manufacture of grease. The oil cake is used as feed and manure. Green stem and leaves var. toria), brown sarson (Brassica campestris L. var. brown sarson), yellow sarson (Brassica campestris L. var. yellow sarson), Indian mustard [Brassica juncea (L.) Czern & Coss], black mustard (Brassica nigra) and taramira (Eruca sativa /vesicaria Mill.), which have been grown since about 3,500 BC along with nontraditional species like gobhi sarson (Brassica napus L.)and Ethiopian mustard or karanrai (Brassica carinata A. Braun).